Respostas

  • Usuário do Brainly
2014-06-07T23:19:17-03:00
Se  y=x²-bx+7  e x=1
                          y=-1
vamos substituir
fica:
-1=1²-b+7
b=7 +1 +1
b=9

b)y=-2x²-bx+c      sendo y=-4
                                     x= 1
                               b+c= 4
substituir
-4= -2(1)² -b(1) +c
-4= -2 -b +c
b -c=2

vamos formar um sistema
b -c=2
b+c=4
cancelando o c , fica
2b=6
b=6/2
b=3

se b=3 substituindo em b+c=4
                 fica              3+c=4
                                         c=1
R: b=3 e c=1

4 4 4